Genetic diversity and known virulence genes in Listeria innocua strains isolated from cattle abortions and farm environment - Silva Gradovska; Žanete Šteingolde; Juris Ķibilds; Irēna Meistere; Jeļena Avsejenko; Madara Streikiša; Laura Alksne; Margarita Terentjeva; Aivars Bērziņš (Veterinary and Animal Science, 2023)
Listeria innocua is considered as non-pathogenic bacteria living in an environment although several cases of immunocompromised humans and ruminant listeriosis infections have been reported. Previously, L. innocua was identified as a potential pathogen and virulence in association with L. monocytogenes PrfA dependent virulence (LIPI-1) gene cluster was demonstrated in hemolytic L. innocua. L. innocua usually considered non-pathogenic versus pathogenic L. monocytogenes and L. ivanovii because of the main virulence gene loss. There are limited studies and reports available about L. innocua-caused illness in cattle. A total of 18 STs were identified in cattle abortions while 17 STs in the farm environment with majority of STs were present in both abortions and environmental samples. Genome sequencing showed that in one farm identical L. innocua clones were represented in water, feed, soil, and faeces sample groups, suggesting that animals most likely through the faecal shedding may remain as the main source of L. innocua in a farm environment. Out of all L. innocua isolates PrfA-dependent virulence genes were not found in aborted foetuses isolates and environmental L. innocua isolate groups; however, in 20% of isolates a complete LIPI-3 pathogenicity island encoding listeriolysin S was identified. In this study, we demonstrated that genetically diverse L. innocua clones were widely distributed in cattle farm environment and certain isolates had a significant pathogenicity potential for cattle, thus causing adverse health effects, including abortions.